ANALISIS PENGARUH BELANJA PEGAWAI, BELANJA BARANG DAN BELANJA MODAL TERHADAP REALISASI PENERIMAAN PAJAK DI INDONESIA - Tria Sandi Kurniawan; Dyah Reni Irmawati (MediaTrend, 2021)
This study examines the effect of the realization of government spending consisting of goods expenditure, capital expenditure and employee expenditure on tax revenue in Indonesia. In this study, we use four analytical methods that consist of  Granger Test, Partial Adjustment Model (PAM), Error Correction Model (ECM) and Vector Autoregression (VAR). The result shows that the realization of goods and employee expenditure are significant determinant of the tax revenue. Further examination shows that the shocks on goods and employee expenditure havea positive impacts toward tax revenue. However the shock effects are different on those variables. On the shock to goods expenditure, the tax revenue response will occur directly, in contrast to shock on employee expenditure that requires time lag. This study also finds that between PAM and ECM, the ECM model is more appropriate to be used to explain the effect of government spending on tax revenue in Indonesia.